Preparation method of GF / nHA / PA66 bone repair 3D printing raw material
Through the preparation method of 3D printing raw materials for GF/nHA/PA66 bone repair, the problem of insufficient mechanical properties and injection molding of nanoHAP/PA66 composite materials is solved, and higher mechanical strength and biocompatibility are achieved to meet the specific needs of bones. Promotes the osteogenesis process in the body.
Patent Information
- Application Number
- CN202411149379.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-21
- Publication Date
- 2024-12-13
AI Technical Summary
The mechanical properties of existing nanoHAP/PA66 composites in the human body are not ideal, and injection molding is difficult to meet the specific needs of bones, resulting in the sacrifice of biomechanical properties.
The preparation method of 3D printing raw materials for bone repair by using GF/nHA/PA66, stirring CaCl2 into anhydrous ethanol and PA66, adding nano-hydroxyapatite and glass fibers to form a GF/nHA/PA66 solution, which is washed and dried After that, high-temperature wire drawing treatment is carried out to ensure uniform dispersion and mechanical strength of the material.
The mechanical strength and biocompatibility of the composite material are improved, the stability and osteogenic ability in the organism are ensured, and the distribution of nano HA is not affected, and the biotoxicity of CaCl2 is reduced.
Smart Images

Figure CN119113228A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of biomedical materials, and in particular to a method for preparing GF / nHA / PA66 bone repair 3D printing raw materials. Background Art
[0002] In recent years, the orthopedic consumables market has grown rapidly, and medical bone repair biomaterials have always been a research hotspot in the biomedical field. Hydroxyapatite (HAP) is the main inorganic component of human bones and teeth, with a content of 60% to 65% in bones. It has good biological activity and osteoconductivity, but its poor toughness and brittle fracture limit its application in human body load-bearing bones. Polyamide (PA) is one of the important engineering plastics, with a similar structure to collagen, polar amide bonds (—NH—CO—), and good biocompatibility. PA66 in the polyamide series has good toughness. Therefore, filling HAP with a high elastic modulus into a strong and tough PA matrix can obtain a composite material with excellent biological activity and comprehensive performance. Hard tissue bone repair materials require long-lasting mechanical properties in the body, but the large number of amide groups in the PA66 molecular structure easily form hydrogen bonds with water molecules and absorb moisture in the environment. The water absorption rate is about 1.8% in 23℃ water for 24 hours, which causes the nanoHAP / PA66 composite material to be dimensional unstable during use and its mechanical properties to drop sharply, thus greatly shortening the product life.
[0003] In order to improve the water absorption of PA66, non-polar polymers such as polyethylene (PE) and polypropylene (PP) with extremely low water absorption are usually added. Due to the difference in thermodynamic compatibility between PA66 and PP and PE, various compatibilizers such as polyethylene grafted maleic anhydride and polypropylene grafted maleic anhydride need to be added to improve the compatibility between polymers. Any compatibilizer can only play a compatibilizing effect to a certain extent. There is an obvious interface between the non-polar polymer and polyamide, which leads to a significant decrease in the mechanical properties of the composite material.
[0004] However, when organic and inorganic multiphases are composited, the two phases must be fully combined to achieve the best composite material performance, and it is difficult for crystalline PA to be fully combined with HA. CN105031720A adds PA to an anhydrous ethanol solution containing CaCl2 to obtain a PA solution, and then disperses the HA powder prepared by calcination in anhydrous ethanol to obtain a HA dispersion, adds the HA dispersion to the PA solution, adds water and stirs, and finally obtains a nano-hydroxyapatite-polyamide medical composite material. However, the composite material was later injection molded, and it was found that due to the poor mechanical properties of the composite material, it was difficult to perform injection molding.
[0005] CN111154256A discloses a method for preparing a nano-hydroxyapatite / polyamide composite material, which comprises the following steps: (1) adding polyamide to anhydrous ethanol containing CaCl2, heating and dissolving, and obtaining a polyamide solution; (2) adding nano-hydroxyapatite to anhydrous ethanol to obtain a hydroxyapatite dispersion; (3) adding the hydroxyapatite dispersion to the polyamide solution for compounding, and after the compounding is completed, injecting the slurry into water, stirring, precipitating, solid-liquid separation, washing and drying, and granulation to obtain the composite material. The compressive strength and impact strength of the composite material prepared by this method are improved, but the mechanical properties are still not ideal, and its compressive strength needs to be improved.
[0006] In addition, since bones in different parts of the human body have certain shapes, densities, and microstructure specificities, existing processing methods such as injection molding are difficult to simultaneously meet the above characteristics, or existing nanoHAP / PA66 composite materials will inevitably sacrifice some biomechanical properties when meeting the specificity of bones at the implantation site. Therefore, the present invention adopts the method of adding micron-grade glass fibers to the nanoHAP / PA66-based composite material to evenly distribute them in the mixed system, so as to simultaneously meet the 3D printing requirements and the physiological and mechanical requirements of bones at the implantation site. Summary of the invention
[0007] In order to solve the above technical problems, the present invention provides a method for preparing GF / nHA / PA66 bone repair 3D printing raw materials.
[0008] The technical scheme is as follows: A method for preparing GF / nHA / PA66 bone repair 3D printing raw materials, characterized in that it comprises the following steps:
[0009] S1: Dissolve CaCl2 in anhydrous ethanol until it is completely melted, then add PA66 and continue stirring to obtain a PA66 solution. Polyamide 66, a polymer with higher mechanical strength, is used as the base material, which can greatly improve the mechanical strength of the 3D printed bracket;
[0010] S2: Weigh nHA (nanohydroxyapatite slurry) and GF (glass beads) and dissolve them in anhydrous ethanol without heating and stirring to prepare a GF / nHA mixed dispersion;
[0011] S3: After PA66 is completely dissolved in anhydrous ethanol, the prepared GF / nHA mixed dispersion is added, and the reaction is continued under stirring under continuous heating to obtain a GF / nHA / PA66 solution;
[0012] S4: After the reaction is completed, pour the GF / nHA / PA66 solution obtained in step S3 into a clean beaker, wait for it to cool naturally to room temperature, add purified water, and precipitate the reaction mixture;
[0013] S5: Pour out the supernatant after precipitation in step S4, continue to add pure water, and dispense into centrifuge tubes to centrifuge and wash the CaCl2 in the GF / nHA / PA66 solution until no white precipitate is precipitated when the supernatant reacts with AgNO3; wash out a large amount of CaCl2 used to dissolve PA66 to reduce the biological toxicity caused by excessive chloride ion load in the mixed material. Because in the preparation method, CaCl2 is used as an activator to interrupt the abundant hydrogen bonds in PA66, making it more soluble in anhydrous ethanol.
[0014] S6: drying the washed mixture in an oven to obtain a GF / nHA / PA66 mixture raw material;
[0015] S7: The GF / nHA / PA66 mixture raw material is ground and crushed by a planetary ball mill and then subjected to high-temperature wire drawing by a twin-screw extruder. After wire drawing, the temperature is naturally cooled. The cooled pellets can be 3D printed to prepare bioactive bone repair scaffolds.
[0016] Preferably: in step S1, the CaCl2 is dissolved in anhydrous ethanol and is continuously heated and stirred at a temperature of 85-95°C and a stirring speed of 200 r / min;
[0017] Preferably, the mass ratio of CaCl2:PA66 is (1.8-2.8):1, and the stirring time is 10.0-11.0 hours.
[0018] Preferably: the water content of the nHA slurry in the S2 step is about 70%, the particle size of GF is <20um, and the nHA used is a water-containing slurry rather than nHA powder, which is more conducive to uniform dispersion of nHA in the mixed material. GF with a particle size of <20um can enhance the mechanical properties of the material while meeting the requirements of 3D printing based on FDM technology.
[0019] Preferably, in the GF / nHA / PA66 solution obtained in step S3, the mass ratio of PA66:nHA is (5-7):(3-5), and GF accounts for 4% of the total mass of the system.
[0020] Preferably, the stirring temperature in step S3 is 85-95° C., the stirring speed is 200 r / min, and the stirring time is 2.0-3.0 hours.
[0021] Preferably: the concentration of AgNO3 in step S5 is 0.065 mol / L, and the white precipitate is AgCl.
[0022] Preferably, the oven temperature in step S6 is set to 80°C.
[0023] Preferably, the temperature of the high-temperature wire drawing treatment in step S7 is 265-295°C.
[0024] Compared with the prior art, the present invention has the following beneficial effects: the present invention is different from the previous preparation method in that the chemical melting method is used for the reaction, the system is more evenly dispersed, a certain amount of hydrogen bonds are formed, and the system is more stable and stronger than the ordinary physical mixing method. While not changing or even optimizing its biocompatibility and biological activity, its mechanical properties are further enhanced;
[0025] The 4% GF / nHA / PA66 composite material has better mechanical strength and does not affect the distribution of nHA, and can effectively promote osteogenesis in vivo; the composite material extract has no obvious toxic effect on the MC3T3-E1 cells co-cultured with it, and does not have a negative effect on cell proliferation. The cells on the 4% GF / nHA / PA66 composite material show fusion, agglomeration and stratification, and the expression of intracellular actin filaments and type I collagen is good. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a schematic diagram of the process of the present invention;
[0027] Figure 2 This is the SEM image of glass fiber nano-hydroxyapatite polylactic acid ternary composite material;
[0028] Figure 3 This is the SEM image of 4% GF / nHA / PA66 ternary composite material;
[0029] Figure 4 Print example images for porous structure samples;
[0030] Figure 5 SEM images of nHA / PA66 and 4% GF / nHA / PA66;
[0031] Figure 6 It is a line graph of the absorbance values of different composite materials at different times;
[0032] Figure 7 This is a graph showing the expression of osteogenic-related proteins in MC3T3-E1 cells under the action of each group of composite materials. DETAILED DESCRIPTION
[0033] The present invention is further described below in conjunction with embodiments and drawings.
[0034] like Figure 1 As shown, Example 1
[0035] A method for preparing GF / nHA / PA66 bone repair 3D printing raw materials, comprising the following steps:
[0036] S1: Dissolve CaCl2 in anhydrous ethanol (under continuous heating and stirring, 85°C, 200r / min), and after it is completely melted, add PA66, the mass ratio of CaCl2:PA66 is 1.8:1, and continue to add and stir for 10 hours;
[0037] S2: Weigh nanohydroxyapatite slurry (nHA) and glass microbeads (GF, particle size <20um), dissolve them in anhydrous ethanol without heating and continuously stirring to prepare a nanohydroxyapatite / glass fiber mixed dispersion; the water content coefficient of the nHA slurry is about 70%, and attention should be paid to the conversion mass when weighing nHA;
[0038] S3: After PA66 is completely melted in anhydrous ethanol, add the prepared nano-hydroxyapatite / glass fiber mixed dispersion and continue to stir and react under continuous heating at 85°C, 200r / min, for 2 hours; wherein the mass ratio of PA66:nHA is 7:3, and GF accounts for 4% of the total mass of the system;
[0039] S4: After the reaction is completed, pour the GF / nHA / PA66 solution obtained in step S3 into a clean beaker, wait for it to cool naturally to room temperature, add purified water (no special requirement, as much as possible), and precipitate the reaction mixture;
[0040] S5: Pour out the supernatant after precipitation, continue to add pure water, and dispense into centrifuge tubes for centrifugal cleaning of CaCl2 in the GF / nHA / PA66 solution (you can also use a vacuum filtration device to filter instead of this step to optimize the cleaning method), and clean until the supernatant reacts with 0.065mol / LAgNO3 and no white precipitate (AgCl) is precipitated;
[0041] S6: drying the washed mixture in an oven at 80° C. to obtain a GF / nHA / PA66 mixture raw material;
[0042] S7: The raw materials of the mixture are ground and crushed by a planetary ball mill and then subjected to high-temperature wire drawing by a twin-screw extruder at a temperature of 265°C. After wire drawing, the mixture is naturally cooled. The cooled pellets can be 3D printed (FDM) to prepare bioactive bone repair scaffolds.
[0043] Example 2
[0044] A method for preparing GF / nHA / PA66 bone repair 3D printing raw materials, comprising the following steps:
[0045] S1: Dissolve CaCl2 in anhydrous ethanol (under continuous heating and stirring, 90°C, 200r / min), and after it is completely melted, add PA66, the mass ratio of CaCl2:PA66 is 2.4:1, and continue to add and stir for 10.5 hours;
[0046] S2: Weigh nanohydroxyapatite slurry (nHA) and glass microbeads (GF, particle size <20um), dissolve them in anhydrous ethanol without heating and continuously stirring to prepare a nanohydroxyapatite / glass fiber mixed dispersion; the water content coefficient of the nHA slurry is about 70%, and attention should be paid to the conversion mass when weighing nHA;
[0047] S3: After PA66 is completely melted in anhydrous ethanol, add the prepared nano-hydroxyapatite / glass fiber mixed dispersion and continue to stir and react under continuous heating at 90°C, 200r / min, for 2.5 hours; wherein the mass ratio of PA66:nHA is 6:4, and GF accounts for 4% of the total mass of the system;
[0048] S4: After the reaction is completed, pour the GF / nHA / PA66 solution obtained in step S3 into a clean beaker, wait for it to cool naturally to room temperature, add purified water (no special requirement, as much as possible), and precipitate the reaction mixture;
[0049] S5: Pour out the supernatant after precipitation, continue to add pure water, and dispense into centrifuge tubes for centrifugal cleaning of CaCl2 in the GF / nHA / PA66 solution (you can also use a vacuum filtration device to filter instead of this step to optimize the cleaning method), and clean until the supernatant reacts with 0.065mol / LAgNO3 and no white precipitate (AgCl) is precipitated;
[0050] S6: drying the washed mixture in an oven at 80° C. to obtain a GF / nHA / PA66 mixture raw material;
[0051] S7: The raw materials of the mixture are ground and crushed by a planetary ball mill and then subjected to high-temperature wire drawing by a twin-screw extruder at a temperature of 280°C. After wire drawing, the temperature is naturally cooled. The cooled pellets can be 3D printed (FDM) to prepare bioactive bone repair scaffolds.
[0052] Example 3
[0053] A method for preparing GF / nHA / PA66 bone repair 3D printing raw materials, comprising the following steps:
[0054] S1: Dissolve CaCl2 in anhydrous ethanol (under continuous heating and stirring, 90°C, 200r / min), and after it is completely melted, add PA66, the mass ratio of CaCl2:PA66 is 2.8:1, and continue to add and stir for 11.0 hours;
[0055] S2: Weigh nanohydroxyapatite slurry (nHA) and glass microbeads (GF, particle size <20um), dissolve them in anhydrous ethanol without heating and continuously stirring to prepare a nanohydroxyapatite / glass fiber mixed dispersion; the water content coefficient of the nHA slurry is about 70%, and attention should be paid to the conversion mass when weighing nHA;
[0056] S3: After PA66 is completely dissolved in anhydrous ethanol, the prepared nano-hydroxyapatite / glass fiber mixed dispersion is added, and the reaction is continued under stirring at 95°C, 200r / min, for 3.0 hours; wherein the mass ratio of PA66:nHA is 5:5, and GF accounts for 4% of the total mass of the system;
[0057] S4: After the reaction is completed, pour the GF / nHA / PA66 solution obtained in step S3 into a clean beaker, wait for it to cool naturally to room temperature, add purified water (no special requirement, as much as possible), and precipitate the reaction mixture;
[0058] S5: Pour out the supernatant after precipitation, continue to add pure water, and dispense into centrifuge tubes for centrifugal cleaning of CaCl2 in the GF / nHA / PA66 solution (you can also use a vacuum filtration device to filter instead of this step to optimize the cleaning method), and clean until the supernatant reacts with 0.065mol / LAgNO3 and no white precipitate (AgCl) is precipitated;
[0059] S6: drying the washed mixture in an oven at 80° C. to obtain a GF / nHA / PA66 mixture raw material;
[0060] S7: The raw materials of the mixture are ground and crushed by a planetary ball mill and then subjected to high-temperature wire drawing by a twin-screw extruder at a temperature of 295°C. After wire drawing, the mixture is naturally cooled. The cooled pellets can be 3D printed (FDM) to prepare bioactive bone repair scaffolds.
[0061] Test example
[0062] In order to verify that the prepared GF / nHA / PA66 bone repair 3D printing raw materials have better mechanical properties, the following tests can be performed.
[0063] Test Example 1
[0064] Comparing the SEM images of the glass fiber nano-hydroxyapatite polylactic acid ternary composite material and the 4% GF / nHA / PA66 ternary composite material of the present invention, the results are as follows Figure 2 and Figure 3 shown.
[0065] Among them, the glass fiber nano-hydroxyapatite polylactic acid ternary composite materials include P2O5–CaO–MgO–Na2O (P45B0), P2O5–CaO–MgO–Na2O–B2O3 (P45B5), P2O5–CaO–MgO–Na2O–Fe2O3 (P45Fe3) and P2O5–CaO–MgO–Na2O–B2O3–Fe2O3 (P45B5Fe3).
[0066] like Figure 1 Note: It can be seen that there is a lot of nHA / PA66 mixture adhered to the surface of the glass fiber, and nHA is evenly dispersed on the surface of PA66. Based on this, according to the principle of physical layer combination, it can be inferred that the 4% GF / nHA / PA66 ternary composite material is superior to the glass fiber nano-hydroxyapatite polylactic acid ternary composite material in mechanical strength, and does not affect the distribution of nHA, and can effectively promote osteogenesis in vivo.
[0067] Test Example 2 Biomechanics
[0068] The maximum load, bending strength and fracture strength of the prepared 4% GF / nHA / PA66 ternary composite material were measured, and the bending modulus, tensile, bending and cantilever beam impact strength of the glass fiber nano-hydroxyapatite polylactic acid ternary composite material were measured at the same time. The test results are shown in Table 1 below:
[0069] Table 1 Biomechanical tests
[0070]
[0071] Finally, the average maximum load of the 4% GF / nHA / PA66 ternary composite material of the present invention (specimen area 45.084mm2) was measured to be 326N, the average bending strength was 147.24MPa, and the average breaking strength was 139.88MPa; while the bending modulus of the glass fiber nano-hydroxyapatite polylactic acid ternary composite material was 7GPa, and the tensile, bending and cantilever beam impact strengths reached 72MPa, 84MPa and 73MPa respectively.
[0072] Test Example 3 Mechanical Properties Test
[0073] ① Standard mechanical test piece:
[0074] Comparison of mechanical properties of 2% GF / nHA / PA66, 4% GF / nHA / PA66, and 6% GF / nHA / PA66. According to ASTMD3039-76, ASTMD638, ASTMD3410-75, and ASTMD7624 standards, the prepared composite materials were prepared into standard specimens (80mm×40mm×10mm), and their mechanical properties were tested using a universal mechanical testing machine. The results are shown in the table below. Its mechanical parameters match the mechanical properties of natural bones, namely, compressive strength: 90-120MPa; flexural strength: 60-120MPa; elastic modulus: 4-20GPa; elongation at break: 1-3%. The test results are shown in Table 2 below;
[0075] Table 2 Mechanical properties of three composite materials
[0076]
[0077]
[0078] ②3D printing model:
[0079] 1) Melt pressure and droplet adjustment: Under the processing parameters of X% GF / nHA / PA66 composite material, the printer can successfully complete the material cleaning and droplet adjustment, the nozzle discharge is stable and uniform, the wire diameter is about 0.2mm, and the printer can meet the processing requirements of the composite material.
[0080] 2) Printing parameters: The parameters are shown in Table 3;
[0081] Table 3 GF / nHA / PA66 3D printing parameters
[0082] Nozzle temperature / ℃ Barrel temperature 1 / ℃ Barrel temperature 2 / ℃ Discharge volume / % 320 280 260 70 Melt pressure / Mpa Printing frequency / Hz Layer height / mm AR value 380-400 200 0.17-0.2 1.0-1.6
[0083] 3) Printing of porous structure samples: The printer can successfully complete the printing of 3D model porous fusion devices, with complete pore structure and relatively uniform pore distribution. The printer has a good effect on printing simple pore structures, such as Figure 4 and Figure 5 shown.
[0084] 4) Mechanical testing of 3D printed samples: The test results are shown in Table 4 below;
[0085] Table 4 Mechanical test results of 3D printed samples
[0086] sample Diameter / mm Maximum force / N Compression modulus / Mpa Elastic modulus / Mpa nHA / PA66 10 8950 52.879 168.06 2% GF / nHA / PA66 10 12617 75.984 325.94 4% GF / nHA / PA66 10 14531 87.392 462.25 6% GF / nHA / PA66 10 15830 93.398 545.94
[0087] Test Example 4 Biocompatibility
[0088] The composite material extract was prepared according to ISO10993-12:2007 standard, with α-MEM medium containing fetal bovine serum and double antibody solution as the extract, and the mass ratio of the composite material to the medium was 0.2g / ml. When preparing the extract, it should be noted that the composite material must be completely submerged in the medium. In the clean bench, 2% GF / nHA / PA66, 4% GF / nHA / PA66, and 6% GF / nHA / PA66 composite materials were placed in the culture medium and extracted at 37°C for 72 hours. The obtained extract was sealed and placed in a 4°C refrigerator for standby use.
[0089] ① Cell plating
[0090] Observe the cell growth in the cell culture flask used for plating under a microscope. After confirming that there is no abnormality in the cell state, digest the cells in the clean bench and transfer them to a centrifuge tube. After centrifugation, discard the original culture medium, add α-MEM culture medium containing fetal bovine serum and double antibody solution, and mix them gently by blowing. Then use a pipette to take a small amount of cell suspension and drop it on the cell counting plate. Count the cells under a microscope, and then count them at 5×10 3 Pieces / cm 2 The cells were seeded at a density of 100 μg / ml in a 96-well cell culture plate. After seeding, the plate was still placed in CO 2 The cells were cultured in an incubator. After 24 hours, the adhesion and growth of the plated cells were observed under a microscope, and the original culture medium was aspirated. According to the grouping situation, α-MEM culture medium containing fetal bovine serum and double antibody solution and 200 μl of composite material extract were added to the corresponding wells, with 4 wells in each group.
[0091] ② Cell proliferation detection
[0092] The culture cycle was changed to material extract solution for 7 days, and the observation points were the 1st, 4th and 7th days after culture. The operation steps were as follows: under light-proof conditions, 20 μl CCK-8 solution was added to each well of the plate, and the plate was sealed with tin foil. 2 Incubate at 37°C in an incubator for 1 hour. After incubation, measure the absorbance of the sample in the well at 450 nm using an ELISA reader.
[0093] ③ Experimental results
[0094] According to ISO10993:12 standard, the effect of composite material extract on MC3T3-E1 cell proliferation was detected. CCK-8 was used as the detection reagent. The detection time points were 1 day, 4 days and 7 days after the cells were co-cultured with the composite material extract. Figure 6As shown in the figure, with the extension of culture time, the number of cells in the three groups gradually increased. The cell proliferation was detected at each observation time point. The cell proliferation in the 4% GF / nHA / PA66 group was higher than that in the 2% GF / nHA / PA66 and 6% GF / nHA / PA66 groups, and the difference was statistically significant (P<0.05). The test results showed that the composite material extract had no obvious toxic effect on the MC3T3-E1 cells co-cultured with it, and had no negative effect on cell proliferation.
[0095] Test Example 5 Effect of Promoting Bone Differentiation
[0096] (1) Preparation of 4% GF / nHA / PA66 and nHA / PA66 composite extracts
[0097] The composite material extract was prepared according to ISO10993-12:2007 standard, with α-MEM medium containing fetal bovine serum and double antibody solution as the extract, and the mass ratio of the composite material to the medium was 0.2g / ml. When preparing the extract, it should be noted that the composite material must be completely submerged in the medium. In the clean bench, 4% GF / nHA / PA66, 4% CF / nHA / PA66, and nHA / PA66 composites were placed in the culture medium and extracted at 37°C for 72 hours. The obtained extract was sealed and placed in a 4°C refrigerator for later use.
[0098] (2) Immunofluorescence experiment to detect the effect of composite materials on the osteogenic differentiation ability of MC3T3-E1 cells
[0099] Effects of different microporous systems on osteogenesis of 4% GF / nHA / PA66 and 4% CF / nHA / PA66 bone biomaterials: Different microporous systems were designed by 3D printing Φ10mm×2mm discs of 4% GF / nHA / PA66 and nHA / PA66 bone biomaterials. Effects of 4% GF / nHA / PA66 and nHA / PA66 bone biomaterials with different microporous systems on osteoblast adhesion and growth: To study the effect of scaffolds on osteoblast function, the cells used were mouse osteoblast cell line MC3T3-E1. Scanning electron microscopy and laser confocal microscopy were used to observe the adhesion and growth of osteoblasts on the surface of 4% GF / nHA / PA66 and nHA / PA66 scaffolds with different microporous systems, and immunofluorescence staining was used to detect the effect of bone biomaterials on osteoblast differentiation.
[0100] ① Before cell inoculation, 4% GF / nHA / PA66 and 4% CF / nHA / PA66 scaffolds were placed in complete culture medium for 72 h to eliminate bubbles in the scaffolds;
[0101] ②Cell plating: Pre-sterilize 4% GF / nHA / PA66 and nHA / PA66 discs with a diameter of 1.5 cm and a thickness of 0.1 cm by γ-ray. Place the discs in groups in a 6-well plate under a clean bench. The groups are the same as above, with 2 wells in each group. The cell planting density is 2×10 4 / cm 2 10 μL containing 4×10 5 MC3T3-E1 cell suspension was inoculated onto the upper surface of the scaffold. After 45 min of rest, the complete medium was added to cover the scaffold. After 24 h, the complete medium was replaced with osteogenic medium. The scaffold was incubated at 37 °C and 5% CO. 2 Conditions were used for culturing for 1, 3, 7, 14, and 21 days, and half of the osteogenic medium was replaced every 2 to 3 days;
[0102] ③ Sample extraction and fixation: The culture period and observation time point are 24 hours. The cell extraction and fixation operations are carried out under the clean bench, the culture medium in each well is discarded, the small disc of the composite material is taken out and placed in a new well plate, the surface of the composite material is washed three times with PBS, and 4% paraformaldehyde is added to fix the sample to be tested, and fixed at room temperature for 15 minutes.
[0103] ④Cell staining: Detect the expression of type I collagen in cells at various time points to study the effects of different microporous systems of 4% GF / nHA / PA66 and nHA / PA66 bone biomaterials on early and late differentiation of osteoblasts. After fixation, add 0.1% Triton X-100 to permeabilize the cells, and permeabilize at room temperature for 5 minutes. After washing the sample to be tested three times with PBS, add rhodamine-phalloidin staining solution with a working concentration of 50μg / ml, and stain at room temperature in the dark for 30 minutes. After staining, add PBS to wash three times again, and then add DAPI staining solution to stain the nucleus, and stain at room temperature in the dark for 15 minutes. After staining, wash the excess stain with PBS.
[0104] ⑤ Sealing and observation under LSCM: The samples were removed from the staining well plate, and anti-fluorescence quenching liquid was added to seal the samples. The samples were stored away from light, and the morphology, cytoskeleton, and expression of osteogenic-related proteins in MC3T3-E1 cells were observed under LSCM.
[0105] Experimental results: Figure 7 As shown, the expression of osteogenic-related proteins in MC3T3-E1 cells under the action of each group of composite materials was further observed by LSCM. The cell morphology and cytoskeleton could be clearly observed. The cells on the 4% GF / nHA / PA66 composite material showed fusion, aggregation and stratification, and the expression of actin filaments and type I collagen in the cells was good; the cell expression in the nHA / PA66 group was similar.
[0106] The 4% GF / nHA / PA66 composite material has better mechanical strength and does not affect the distribution of nHA, and can effectively promote osteogenesis in the body; the composite material extract has no obvious toxic effect on the MC3T3-E1 cells co-cultured with it, and does not have a negative effect on cell proliferation. The cells on the 4% GF / nHA / PA66 composite material show fusion, agglomeration and stratification, and the expression of intracellular actin filaments and type I collagen is good. Therefore, the 4% GF / nHA / PA66 composite material has a broader development prospect as a raw material for bone repair 3D printing.
[0107] Finally, it should be noted that the above description is only a preferred embodiment of the present invention. Under the guidance of the present invention, ordinary technicians in this field can make various similar expressions without violating the purpose and claims of the present invention, and such changes all fall within the scope of protection of the present invention.
Claims
1. A method for preparing GF / nHA / PA66 bone repair 3D printing raw materials, characterized in that: The following steps are involved: S1: Dissolve CaCl2 in anhydrous ethanol, heat until completely melted, add PA66, and continue stirring to obtain a PA66 solution; S2: Weigh nHA and GF and dissolve them in anhydrous ethanol without heating and stirring to prepare a GF / nHA mixed dispersion; S3: After PA66 is completely dissolved in anhydrous ethanol, the prepared GF / nHA mixed dispersion is added, and the reaction is continued under stirring under continuous heating to obtain a GF / nHA / PA66 solution; S4: After the reaction is completed, pour the GF / nHA / PA66 solution obtained in step S3 into a clean beaker, wait for it to cool naturally to room temperature, add purified water, and precipitate the reaction mixture; S5: pour out the supernatant after precipitation in step S4, continue to add purified water, and dispense into centrifuge tubes for centrifugal cleaning of CaCl2 in the GF / nHA / PA66 solution until no white precipitate is formed when the supernatant reacts with AgNO3; S6: drying the washed mixture in an oven to obtain a GF / nHA / PA66 mixture raw material; S7: The obtained GF / nHA / PA66 mixture raw material is ground and crushed by a planetary ball mill and then subjected to high-temperature wire drawing by a twin-screw extruder. After wire drawing, the temperature is naturally cooled. The cooled pellets can be 3D printed to prepare bioactive bone repair scaffolds.
2. The method for preparing a GF / nHA / PA66 bone repair 3D printing raw material according to claim 1, characterized in that: In the step S1, the CaCl2 is dissolved in anhydrous ethanol and is kept heated and stirred at a temperature of 85-95°C and a speed of 200 r / min.
3. A method for preparing a GF / nHA / PA66 bone repair 3D printing raw material according to claim 1 or 2, characterized in that: The mass ratio of CaCl2:PA66 is (1.8-2.8):1, and the stirring time is 10.0-11.0 hours.
4. The method for preparing a GF / nHA / PA66 bone repair 3D printing raw material according to claim 1, characterized in that: The water content of the nHA slurry in step S2 is about 70%, and the particle size of GF is less than 20 um.
5. The method for preparing a GF / nHA / PA66 bone repair 3D printing raw material according to claim 1, characterized in that: In the GF / nHA / PA66 solution obtained in step S3, the mass ratio of PA66:nHA is (5-7):(3-5), and GF accounts for 4% of the total mass of the system.
6. The method for preparing a GF / nHA / PA66 bone repair 3D printing raw material according to claim 5, characterized in that: The stirring temperature in step S3 is 85-95° C., the stirring speed is 200 r / min, and the stirring time is 2.0-3.0 hours.
7. The method for preparing a GF / nHA / PA66 bone repair 3D printing raw material according to claim 1, characterized in that: The concentration of AgNO3 in step S5 is 0.065 mol / L, and the white precipitate is AgCl.
8. The method for preparing a GF / nHA / PA66 bone repair 3D printing raw material according to claim 1, characterized in that: The oven temperature in step S6 is set to 80°C.
9. The method for preparing a GF / nHA / PA66 bone repair 3D printing raw material according to claim 1, characterized in that: The temperature of the high temperature wire drawing process in step S7 is 265-295°C.
